Bounding the parameters of block‐structured nonlinear feedback systems. (29th September 2011) - Cerone, V.; Piga, D.; Regruto, D.
SUMMARY In this paper, a procedure for set‐membership identification of block‐structured nonlinear feedback systems is presented. Nonlinear block parameter bounds are first computed by exploiting steady‐state measurements. Then, given the uncertain description of the nonlinear block, bounds on the unmeasurable inner signal are computed. Finally, linear block parameter bounds are evaluated on the basis of output measurements and computed inner‐signal bounds. The computation of both the nonlinear block parameters and the inner‐signal bounds is formulated in terms of semialgebraic optimization and solved by means of suitable convex LMI relaxation techniques. The problem of linear block parameter evaluation is formulated in terms of a bounded errors‐in‐variables identification problem. Copyright © 2011 John Wiley & Sons, Ltd.